Biochar pH reduction using elemental sulfur and biological activation using compost or vermicompost - Al-Rabaiai, Ahmed; Menezes-Blackburn, Daniel; Al-Ismaily, Said; Janke, Rhonda; Al-Alawi, Ahmed; Al-Kindi, Mohamed; Bol, Roland (Bioresource technology, 2024)
•Elemental sulfur reduces biochar pH, making it a suitable amendment for arid lands.•Elemental sulfur increases soluble cations, reducing biochar basicity and buffering.•Sulfur alters biochar microbial communities, enhancing nutrient availability.•Compost addition to biochar increases microbial diversity, aiding sulfur oxidation.•Compost increases biochar nutrient availability and sulfur-oxidizing bacteria. This study aimed to improve biochar’s quality for arid land applications by using elemental sulfur as a pH reducer agent co-applied with compost or vermicompost as biological activators. Biochar pH was decreased by the addition of elemental sulfur, with the highest reduction from 8.1 to 7.2 occurring when co-amended with vermicompost. Elemental sulfur increased the water-soluble concentrations of calcium, magnesium, and many other elements, and stimulated substrate-induced respiration, especially when co-amended with vermicompost. The bacterial diversity community structure were significantly affected by all treatments. The Shannon index significantly increased in response to compost and sulfur treatments, while the vermicompost treatments showed higher microbial evenness and equitability diversity indices. Multivariate analyses indicated that elemental sulfur oxidation was associated with specific sulfur-oxidizing bacterial clusters. Integrating biochar with sulfur and (vermi)compost was found to be a promising sustainable technology for managing excessive biochar alkalinity, increasing its fertility and potential for application in aridlands.